PROTOTIPE ALAT MONITORING SUHU DAN KELEMBABAN UDARA BERBASIS IOT MENGGUNAKAN ESP32 DI RUANG ETNOGRAFI MUSEUM PENATARAN - Mi’rajtania, Septia; Yuana, Haris; Puspitsari, Wahyu Dwi (Purifikasi, 2025)
The museum is a cultural preservation institution that stores various valuable collections, including the Ethnography room of the Penataran Museum which stores ethnographic objects with high cultural value. To maintain the condition of the collection, real-time environmental monitoring is required, especially temperature and humidity. This study aims to design and implement a prototype of an Internet of Things (IoT)-based air temperature and humidity monitoring tool using an ESP32 microcontroller and a DHT22 sensor. The method used in this study is Research and Development (R&D), with stages of design, assembly, and system testing. The test results show that the tool works according to its function, with accurate temperature and humidity data and an effective system response in responding to environmental changes. Thus, this tool is able to provide an efficient monitoring solution and support efforts to preserve museum collections sustainably.